THE RELATION BETWEEN OIL PRODUCTION AND THE CO2 EMISSIONS OF THE MANUFACTURING SECTOR: A DECOMPOSITION ANALYSIS OF MEXICO´S INDUSTRY FROM 1970-2010 - Puyana-Mutis, Alicia; Santillán-Vera, Mónica; Pérez-Guzmán, Katya (European Scientific Journal, ESJ, 2014)
Climate change mitigation public policyrequires a honed diagnosis of the main drivers of its greenhouse gases emissions. The natural resource curse theory, NRC, proposes that the production, consumption and exports of oil could induce a myriad of negative economic and social effects. The carbon curse postulate, on the other hand, suggests higher carbon intensity What the NRC has not addressed, so far, is the relationship between hydrocarbonsexploitation andCO2 emissions. Decomposition analysis has been used by various authors to analyze national energy consumption and emissions, but they have not so far mined the possible relationships between the resource abundance and CO2 emissions. This paper attempts to fill this gap by studying the main drivers of Mexico´s manufacturing sector CO2 emissionsfrom 1970 to 2010, period in which there are important discoveries of oil and changes in the oil production, as well as in the economic context. Manufactures are purportedly impacted by oil abundance, inside the NRC literature. Although the period of analysis spans four decades, smaller sub-periods are analyzed to look for subtler changes in energy use and emissions trends. The results show that after the 1982 oil boom, there were several decreasing effects in the manufacturing industry, giving support to a resource curse hypothesis. However, the Carbon Index measure of the Chemicals, Petrochemicals and Cement subsectors remain high after the boom, accounting for the possible high carbon intensity effects proposed by the carbon curse hypothesis.